Simplify the expression. (1.08×10−3)×(9.3×10−3)÷0.1
2 answers:
Well i think the answer is
(1.08 x 10^-3) * (9.3x10^-3) = 10.044 x 10^-6
.01 = 10x10^-2
10.044 x 10^-6
--------------------- = 1.0044 x 10^-4
10 x 10^-2
You might be interested in
Answer:
x = -14
Step-by-step explanation:
= -7
multiply 2 on both sides
the 2's cancel out on the fraction side, leaving x = -7(2)
multiply -7 and 2 to get -14
x = -14
Answer:
You have 2 mystery boxes and you add them to 3 mystery bags. Each has a different amount of things represented by a and b.
Step-by-step explanation:
f(x) *g(x) = (x-3)(x+11) = x^2 +11x -3x -33 = x^2 +8x -33
Sorry if its wrong :(
Next 7 days
amount needed-amount now=amount in each day200-148=52
52 in 7 daysdivide by 752/7=7.4285round7.43
need to earn about $7.43 each day
Answer:
My favourite color is The Red and White;)
What's yours?
don't forget to like and mark me